2021
DOI: 10.1093/nar/gkab927
|View full text |Cite
|
Sign up to set email alerts
|

THUMPD3–TRMT112 is a m2G methyltransferase working on a broad range of tRNA substrates

Abstract: Post-transcriptional modifications affect tRNA biology and are closely associated with human diseases. However, progress on the functional analysis of tRNA modifications in metazoans has been slow because of the difficulty in identifying modifying enzymes. For example, the biogenesis and function of the prevalent N2-methylguanosine (m 2 G) at the sixth position of tRNAs in eukaryotes has long remained enigmatic. Herein, using a reverse genetics approach coupled with RNA-mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…In the study, we reported that the THUMP domain in T. kodakarensis Trm11 recognizes the CCA terminus in tRNA [ 8 ]. The recognition of the 3′-end of substrate tRNA by a THUMP domain has also been reported for other tRNA modification enzymes [ 8 , 9 , 10 , 19 , 20 ]. For example, the crystal structure of complex of Thermotoga maritima ThiI (tRNA 4-thiouridine synthetase) and truncated tRNA revealed that the THUMP domain in ThiI captures the 3′-terminal region in tRNA [ 20 ].…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…In the study, we reported that the THUMP domain in T. kodakarensis Trm11 recognizes the CCA terminus in tRNA [ 8 ]. The recognition of the 3′-end of substrate tRNA by a THUMP domain has also been reported for other tRNA modification enzymes [ 8 , 9 , 10 , 19 , 20 ]. For example, the crystal structure of complex of Thermotoga maritima ThiI (tRNA 4-thiouridine synthetase) and truncated tRNA revealed that the THUMP domain in ThiI captures the 3′-terminal region in tRNA [ 20 ].…”
Section: Resultsmentioning
confidence: 57%
“…Trm11 is a typical Rossmann fold S-adenosyl-L-methionine (AdoMet)-dependent methyltransferase (COG 1041) with a thiouridine synthase, methyltransferase and pseudouridine synthase (THUMP) domain fused to its N-terminal region [ 4 , 5 , 8 , 9 , 10 ]. The THUMP domain is frequently observed in tRNA modification enzymes [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and is often required for binding to the CCA terminal region of tRNA [ 8 , 9 , 10 , 19 , 20 ]. In the Trm11-Trm112 complex, Trm112 activates the tRNA methyltransferase activity of Trm11 [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed three biological replicates and, in all cases, seven MTases with H/L ratios ranging from 5 to 24 were pulled down (Figure 1D). Among these proteins were the already known TRMT112 interaction partners WBSCR22 [9,13], N6AMT1 [20], ALKBH8 [26], METTL5 [10] and THUMPD3 [29], but also novel, uncharacterised proteins THUMPD2 and TRMT11. THUMPD2 is specific to mammalian cells, but TRMT11 homologue in yeast Trm11 is a tRNA MTase [30].…”
Section: Identification Of Trmt112 Interaction Partnersmentioning
confidence: 99%
“…THUMPD3, together with TRMT112, is a m 2 G methyltransferase working on a broad range of tRNA substrates. THUMPD3-knockout cells exhibit an impaired global protein synthesis and reduced growth [29].…”
Section: Introductionmentioning
confidence: 99%